2017
DOI: 10.1109/tnsre.2017.2748388
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Classification From EEG Signals Using Transfer Learning, Semi-Supervised Learning and TSK Fuzzy System

Abstract: Recognition of epileptic seizures from offline EEG signals is very important in clinical diagnosis of epilepsy. Compared with manual labeling of EEG signals by doctors, machine learning approaches can be faster and more consistent. However, the classification accuracy is usually not satisfactory for two main reasons: the distributions of the data used for training and testing may be different, and the amount of training data may not be enough. In addition, most machine learning approaches generate black-box mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(107 citation statements)
references
References 38 publications
0
102
0
Order By: Relevance
“…It has been suggested that personalisation may be especially useful when using data from noisy modalities, such as wearable devices 116 . Model personalising has been successfully applied in other fields, such as mood recognition 117 and seizure detection 118 . However, it remains relatively untapped in sleep science.…”
Section: Conventional Sleep Classification Methodsmentioning
confidence: 99%
“…It has been suggested that personalisation may be especially useful when using data from noisy modalities, such as wearable devices 116 . Model personalising has been successfully applied in other fields, such as mood recognition 117 and seizure detection 118 . However, it remains relatively untapped in sleep science.…”
Section: Conventional Sleep Classification Methodsmentioning
confidence: 99%
“…The epileptic seizure-free EEG signals in datasets C and D were also produced, accordingly. Dataset E describes the epileptic seizure signals, which were collected by placing the electrodes in the epileptogenic zone, as shown in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43]. The sample segment of each dataset is shown in Figure 1.…”
Section: Eeg Data Materialsmentioning
confidence: 99%
“…A confusion matrix generally involves the following parameters: The following aggregate metrics can then be calculated based on the above parameters. The criteria for performance evaluation are usually employed in biomedical studies, which include three parts: sensitivity (the proportion of the total number of labeled ictal EEGs that are correctly classified), specificity (the proportion of the total number of labeled inter-ictal EEGs that are correctly classified), and classification accuracy (the proportion of the total number of EEG signals that are correctly classified) [2,[6][7][8][9][10][13][14][15][16][25][26][27][28][29][30][31][32]34,35,[38][39][40][41]49,53,59].…”
Section: Performance Evaluation-confusion Matrix Metricsmentioning
confidence: 99%
See 2 more Smart Citations